Status epilepticus. Issue 6 (1st December 2005) - Kelso, A. R. C.; Cock, H. R.
Abstract : INTRODUCTION Epilepsy is the most common serious neurological disorder, affecting approximately 1 in 150 people in the UK (Sander 2003), and status epilepticus is sometimes described as the maximal expression of epilepsy, being associated with both short- and long-term significant mortality and morbidity. Learning about its treatment should represent a significant portion of training in acute general internal medicine, and a good understanding is essential for any general or epilepsy neurologist. In this review we will discuss the epidemiology, treatment and outcome of status epilepticus, in the context of best available evidence and nationally and internationally agreed guidelines. Although there are almost as many types of status as there are of seizures (Table 1), we will concentrate on tonic-clonic status but will also make some mention of non-convulsive status epilepticus and epilepsia partialis continua. Forms of status epilepticus specific to childhood (e.g. febrile status) will not be discussed in any